The correlation between children’s song and memorizing vocabulary to young learner as foreign language on kindergarten - Miftahul Muttaqiin (Universitas Negeri Padang, 2020)
The problems in this research is children’s song related to memorize vocabulary to young learner and how how significance is the correlation between children song and memorizing vocabulary to young learner as foreign language of kindergarten PKK Polagan Pamekasan Madura. This research used quantitative approach, while the kind of research used non-experimental design that is correlation design. Population of this research is all of the students in TK PKK Polagan Pamekasan 2020/2021 that consist of 28 students. The obtained data from questionnaire, test and documentation. The obtained data analyzed by using statistical analysis that used product moment. The result of this study showed that the use of children song related to memorizing vocabulary to young learner as foreign language of kindergarten PKK Polagan Pamekasan. This case has proven from the result of “r” value is 0.711 higher than “r” table in level significance 5% and 1% with N = 28 is 0.374 and 0.478 and it is proven from the interpretation of “r” product moment that the result is between 0,600 – 0,800 in the level of enough correlation. Based on the result above, the researcher concludes that children song can use as strategy in vocabulary learning. This can make the students interest to study and make the students easy to memorize of vocabulary.